Analysis of the Long-Term Corrosion Behavior of X80 Pipeline Steel in Acidic Red Soil Using Electrical Resistance Test Technique - Shuaixing Wang; Daoxin Liu; Nan Du; Qing Zhao; Jinhua Xiao (Advances in Materials Science and Engineering)
The long-term corrosion rate of X80 steel in an acidic red soil was monitored in situ by using a precise electrical resistance (ER) test system. The corrosion characteristics of X80 steel were examined via SEM, EDS, and XRD. The results indicated that the corrosion rate determined from ER test was very similar to that obtained from the mass loss test. The ER test technique made it possible to predict the long-term corrosion rate of steel in soil in situ. The corrosion rate of X80 steel in acidic red soil was about 0.0902 mm/a at 38 weeks, but the corrosion rate was dropped to 0.0226 mm/a after 5 years. The final corrosion product layer was composed mainly of FeOOH, γ-Fe2O3, and FeCO3.